Evaluation of the Effect of Financial Ratios on Sukuk Rating: The Moderating Role of Debt Equity Ratio (DER) - Nurhasanah, Nurhasanah; Melzatia, Shinta (Journal of Islamic Economics and Social Science (JIESS), 2022)
Bond or sukuk ratings have an important meaning for companies and investors, because the bond / sukuk rating is an indicator of the risk of default. Sukuk as an alternative investment is increasingly in demand by investors in Indonesia. But unfortunately, some bonds and sukuk have defaulted in 2019. This study aims to determine the effect between current ratio (CR), total asset turn over (TATO) and return on assets (ROA) on sukuk ratings moderated by Debt Equity Ratio (DER). Sukuk rating is the dependent variable in this study measured by assessment techniques based on Pefindo ratings. This study uses secondary data which is a non-bank company from the Indonesia Stock Exchange and received a rating from Pefindo in 2013-2018. While the sampling method used is the purposive method, namely a total of 84 samples selected. This study uses data analysis methods using Multiple Regression Analysis with hypothesis testing F statistical test and t statistical test, Eviews 9 programme assistance. The conclusions that can be drawn from this study are as follows: (1) Current Asset (CR) has a significant positive effect on sukuk rating; (2) Total asset turn over has a significant negative effect on sukuk rating; and (3) Return on assets does not have a positive effect on sukuk ratings.